Exercise pathophysiology and sildenafil effects in chronic thromboembolic pulmonary hypertension. Issue 8 (16th February 2015) - Claessen, Guido; La Gerche, Andre; Wielandts, Jean-Yves; Bogaert, Jan; Van Cleemput, Johan; Wuyts, Wim; Claus, Piet; Delcroix, Marion; Heidbuchel, Hein
Abstract : Objectives: Symptoms in patients with chronic thromboembolic pulmonary hypertension (CTEPH) predominantly occur during exercise, while haemodynamic assessment is generally performed at rest. We hypothesised that exercise imaging of RV function would better explain exercise limitation and the acute effects of pulmonary vasodilator administration than resting measurements. Methods: Fourteen patients with CTEPH and seven healthy control subjects underwent cardiopulmonary testing to determine peak exercise oxygen consumption (VO2 peak) and ventilatory equivalent for carbon dioxide (VE/VCO2 ) at the anaerobic threshold. Subsequently, cardiac MRI was performed at rest and during supine bicycle exercise with simultaneous invasive measurement of mean pulmonary arterial pressure (mPAP) before and after sildenafil. Results: During exercise, patients with CTEPH had a greater increase in the ratio of mPAP relative to cardiac output (CO) than controls (6.7 (5.1–8.7) vs 0.94 (0.86–1.8) mm Hg/L/min; p<0.001). Stroke volume index (SVi) and RVEF increased during exercise in controls, but not in patients with CTEPH (interaction p<0.001). Sildenafil decreased the mPAP/CO slope and increased SVi and RVEF in patients with CTEPH (p<0.05) but not in controls. In patients with CTEPH, RVEF reserve correlated moderately with VO2 peak (r=0.60; p=0.030) and VE/VCO2 (r=−0.67; p=0.012). By contrast, neither VO2 peak nor VE/VCO2 correlated with resting RVEF. Conclusions: Exercise measures of RV function explain much of the variance in the exercise capacity of patients with CTEPH while resting measures do not. Sildenafil increases SVi during exercise in patients with CTEPH, but not in healthy subjects.